(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The paper attempts to generalize the main problems of the development of the economy of the Republic of Uzbekistan, for which the author analyzes the most important macroeconomic indicators: the formation and structure of GDP, economic growth, the development of private entrepreneurship, inflation, etc. The purpose of the study is to designate the main directions for solving the most acute problems on the way achieving sustainable development of the national economy